A High-Throughput Assay for Screening of Natural Products that Enhanced Tumoricidal Activity of NK Cells. Issue 1 (December 2015) - Gong, Chenyuan; Ni, Zhongya; Yao, Chao; Zhu, Xiaowen; Ni, Lulu; Wang, Lixin; Zhu, Shiguo
Abstract Background Recently, immunotherapy has shown a lot of promise in cancer treatment and different immune cell types are involved in this endeavor. Among different immune cell populations, NK cells are also an important component in unleashing the therapeutic activity of immune cells. Therefore, in order to enhance the tumoricidal activity of NK cells, identification of new small-molecule natural products is important. Despite the availability of different screening methods for identification of natural products, a simple, economic and high-throughput method is lacking. Hence, in this study, we have developed a high-throughput assay for screening and indentifying natural products that can enhance NK cell-mediated killing of cancer cells. Results We expanded human NK cell population from human peripheral blood mononuclear cells (PBMCs) by culturing these PBMCs with membrane-bound IL-21 and CD137L engineered K562 cells. Next, expanded NK cells were co-cultured with non-small cell lung cancer (NSCLC) cells with or without natural products and after 24 h of co-culturing, harvested supernatants were analyzed for IFN-γ secretions by ELISA method. We screened 502 natural products and identified that 28 candidates has the potential to induce IFN-γ secretion by NK cells to varying degrees. Among the 28 natural product candidates, we further confirmed and analyzed the potential of one molecule, andrographolide. It actually increased IFN-γ secretion by NK cells and enhanced NK cell-mediated killing of NSCLC cells. Conclusions Our results demonstrated that this IFN-γ based high-throughput assay for screening of natural products for NK cell tumoricidal activity is a simple, economic and reliable method.